2022
DOI: 10.3390/machines10060457
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of Four Axisymmetrically Distributed Eccentric Rotors in a Vibration System

Abstract: This paper studies synchronization of a class of even pairs and symmetrically distributed eccentric rotors in a vibration system of a single mass body. A vibration system driven by four ERs with circular distribution structure and the same rotating direction is adopted as the dynamic model. The motion differential equations of the system are established based on Lagrange equation. The angular velocity and the phase of each rotor are perturbed by the average value of the synchronous velocity. The state equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Moreover, the changes in phase differences will significantly affect the amplitudes of vibrating bodies. Chen and Liu (2020, 2022) conducted studies on single rigid body vibration systems driven by three or four eccentric rotors. He found that the rotational speed has a significant effect on the stable phase differences before and after the resonant region, and the system can perform two kinds of steady state motions with different phase differences in super-resonant state.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the changes in phase differences will significantly affect the amplitudes of vibrating bodies. Chen and Liu (2020, 2022) conducted studies on single rigid body vibration systems driven by three or four eccentric rotors. He found that the rotational speed has a significant effect on the stable phase differences before and after the resonant region, and the system can perform two kinds of steady state motions with different phase differences in super-resonant state.…”
Section: Introductionmentioning
confidence: 99%